2021
DOI: 10.21580/phen.2021.11.1.8573
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Four-Tier Multiple Choice Diagnostic Test untuk Mengetahui Tingkat Pemahaman Konsep Peserta Didik pada Materi Termokimia

Abstract: Kesulitan peserta didik pada pemahaman materi termokimia melalui suatu proses pembelajaran berpotensi menyebabkan kesulitan peserta didik dalam memahami materi kimia yang lain. Untuk menghindari hal ini, maka perlu dicari letak kesulitan peserta didik dengan tes yang bersifat diagnostik agar dapat diketahui tingkat pemahaman dan kelemahan peserta didik dalam pembelajaran. Penelitian ini bertujuan untuk mengetahui karakteristik dan kualitas instrumen tes diagnostik pilihan ganda empat tingkat yang dikembangkan.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…Several previous studies have shown that a four-tier diagnostic test instrument can be used to analyze the level of misconceptions held by students (Abbas, 2019). Other research shows that the four-tier diagnostic test is valid and appropriate for learning (Roghdah, Zammi, & Mardhiya, 2021;Zaleha, Samsudin, & Nugraha, 2017). Based on the results of previous studies, this diagnostic test is feasible and has been used several times.…”
Section: Introductionmentioning
confidence: 97%
“…Several previous studies have shown that a four-tier diagnostic test instrument can be used to analyze the level of misconceptions held by students (Abbas, 2019). Other research shows that the four-tier diagnostic test is valid and appropriate for learning (Roghdah, Zammi, & Mardhiya, 2021;Zaleha, Samsudin, & Nugraha, 2017). Based on the results of previous studies, this diagnostic test is feasible and has been used several times.…”
Section: Introductionmentioning
confidence: 97%